PENGARUH KUALITAS PELAYANAN MOBILE BANKING TERHADAP LOYALITAS DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA NASABAH BRI - Sintha Yulia Dedari, (2023)
The banking sector has experienced very tight competition which is manifested in the form of competitive creativity and innovation both carried out by government and private banks in attracting customers, so that with the increasing level of competition between banks, banks are increasingly ompeting - competition to get customers by improving service and performance in an integrated way. optimal. This study aims to determine and analyze the effect of mobile banking service quality on loyalty through customer satisfaction. This study uses a questionnaire in data collection conducted on 110 BRI customers who use the BRImo mobile banking service and live or have activities in Jakarta. The analysis technique uses Smart Partial Least Square (PLS) 4.0. As for the results of this study, 1) mobile banking service quality has a direct and significant effect on customer satisfaction, 2) mobile banking service quality has a direct and significant effect on loyalty, 3) customer satisfaction has a direct and significant effect on loyalty, and 4) mobile banking service quality has a direct and significant effect on loyalty and is mediated by customer satisfaction. This means that good service quality can lead to satisfaction. If the service received or felt by the customer matches or even exceeds customer expectations, then the service is considered to be of high quality and satisfactory. When satisfaction has arisen, customer loyalty will be formed.